1992
DOI: 10.1177/0887302x9201100110
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Behavioral Intentions of Agricultural Workers Toward Disposable Protective Coveralls

Abstract: The purpose of this study was to understand better the behavior of grain farmers toward the use of disposable protective coveralls by measuring beliefs, attitudes, and other components of the Fishbein-Ajzen theory of reasoned action and determining relationships among these components. The results indicate that most of the farmers believe that wearing disposable coveralls would provide the best method of protection and a more secure feeling about pesticide use. Respondents believe important referents such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Researchers have also studied attitudes toward catalog apparel purchasing (Eastlick & Feinberg, 1995;Shim & Drake, 1990), apparel advertising (Witter & Noel, 1984, apparel imports (Morganosky & Douglas, 1989), clothing coupons (Cho & Kang, 1998), and apparel markets and their services (Fairhurst, Lennon, & Yu, 1996;Hathcote & Schulte, 1996). From an applied perspective, a number of researchers have examined attitudes toward the use of protective clothing (DeJonge, Vredevoogd, & Henry, 1983-1984Nelson et al, 1988;Perkins et al, 1992;Rucker et al, 1988) by agricultural and lawn care workers. In general, this entire body of research assumes that attitudes toward products and practices lead to decisions about purchase and use.…”
Section: Attitudes Toward Clothing and Shoppingmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also studied attitudes toward catalog apparel purchasing (Eastlick & Feinberg, 1995;Shim & Drake, 1990), apparel advertising (Witter & Noel, 1984, apparel imports (Morganosky & Douglas, 1989), clothing coupons (Cho & Kang, 1998), and apparel markets and their services (Fairhurst, Lennon, & Yu, 1996;Hathcote & Schulte, 1996). From an applied perspective, a number of researchers have examined attitudes toward the use of protective clothing (DeJonge, Vredevoogd, & Henry, 1983-1984Nelson et al, 1988;Perkins et al, 1992;Rucker et al, 1988) by agricultural and lawn care workers. In general, this entire body of research assumes that attitudes toward products and practices lead to decisions about purchase and use.…”
Section: Attitudes Toward Clothing and Shoppingmentioning
confidence: 99%
“…Researchers interested in consumer behavior have often studied attitudes toward clothing (e.g., Atkins & Jenkins, 1988;Chang, Burns, & Noel, 1996;DeLong, Minshall, & Larntz, 1987;Dickson & Littrell, 1996;Francis & Burns, 1992;Koch & Dickey, 1988;Perkins, Crown, Rigakis, & Eggerston, 1992;Shim, Kotsiopulos, & Knoll, 1991). Specific foci of these authors include attitudes toward casual clothing (Chang et al, 1996), "big" sweaters (DeLong et al, 1987), career apparel (Koch & Dickey, 1988), ethnic apparel (Dickson & Littrell, 1996), and sportswear (Atkins & Jenkins, 1988).…”
Section: Attitudes Toward Clothing and Shoppingmentioning
confidence: 99%
“…An overall attitude score was calculated for each participant. Farmers" clothing practices were addressed by questions adapted from (Perkins, Crown, Rigakis, & Eggertson, 1992). Clothing practices included questions about farmers" actual behaviors, including their work clothes worn while mixing pesticides, applying pesticides, and cleaning contaminated equipment, comfort and restriction regarding work clothes, location of donning and doffing, methods of laundering, and storage of contaminated work clothes.…”
Section: Interview Questionsmentioning
confidence: 99%
“…In a study of Alberta farmers focusing on their attitude towards the use of disposable protective coveralls during exposure to pesticides, it was found that the system was being rejected on the premise that it was perceived to be costly; further analysis revealed that the users had misconceptions about the necessity of the level of protection, and placed comfort and convenience at a higher priority (Perkins et al, 1992). When the functionality of the garment system is not transparent to the target user, such as in the case of the Alberta farmers, the users can be deterred from integrating the protective clothing system as a necessary tool into their particular industry.…”
Section: Clothing Systems and Protectionmentioning
confidence: 98%